DQA1*0102 DQB1*0602 haplotype distinguishes coeliac disease and its complications from gluten unrelated enteropathies. Issue 1 (7th November 2022) - De Silvestri, Annalisa; Schiepatti, Annalisa; Fowler, Bryce D; Badulli, Carla; Belvisi, Fabrizio; Cacciatore, Rosalia; Pasi, Annamaria; Zingone, Fabiana; Goodwin, John; Key, Tim; Rej, Anupam; Sanders, David S; et al.
Abstract : Background: Duodenal villous atrophy is due not only to coeliac disease and its complications but also to other rare enteropathies unrelated to gluten consumption, defined as noncoeliac enteropathies. The diagnosis of noncoeliac enteropathies remains challenging, and HLA typing has been widely used to exclude coeliac disease if DQ2 and DQ8 alleles are absent. However, the frequency of the various HLA alleles in noncoeliac enteropathies is still unknown. Aims: To describe the HLA genetic profile of patients affected by noncoeliac enteropathies who have been evaluated at our centres between 2000 and 2021, and to investigate the diagnostic role of HLA typing. Methods: Genomic DNA was collected from 44 Italian and 19 British adult patients with noncoeliac enteropathies. Patient genotypes were compared with those of healthy Italian and British populations obtained from HLA bone marrow donors' banks. In addition, genotypes were also compared with those of patients with coeliac disease and complicated coeliac disease. Results: Both in the Italian and in the British group, the DQA1*0102 DQB1*0602 haplotype and related alleles occurred significantly more frequently in patients with noncoeliac enteropathies compared to coeliac disease and complicated coeliac disease. Conclusions: Together with negative HLA-DQ2 and DQ8 haplotypes, the DQA1*0102 DQB1*0602 haplotype can be used to guide the differential diagnosis between coeliac disease and noncoeliac enteropathies.